Identification and Genetic Characterization of a Novel Respirovirus in Alpine Chamois (Rupicapra rupicapra rupicapra) - Luzzago, Camilla (Animals (Basel), 2020)
SIMPLE SUMMARY: The Alpine chamois is a free-living wild ruminant distributed across the mountainous areas of France, Italy, Switzerland, Liechtenstein, Germany, Austria, Slovenia and Croatia. This wide distribution favours interactions with other wild ruminants and livestock, implying the risk of cross-transmission of pathogens. Due to the impact of lung diseases on chamois populations, the investigation of respiratory pathogens is important for wildlife conservation and for the understanding of infection transmission at the livestock–wildlife interface. In the present study, a novel respirovirus was isolated from a chamois with lung lesions and characterized by full-genome sequence and phylogeny. The genome characterization of this novel virus revealed similarities to domestic ruminant respiroviruses, mainly of caprine and ovine origin. Overall, phylogenetic analyses indicated that the chamois virus is distinct from already defined species and suggested that it is a putative novel member of the genus Respirovirus. The present investigation contributes to the knowledge of respiratory infections in wild ruminants and raises questions on the epidemiological link between chamois and other animal species. ABSTRACT: The Respirovirus genus, family Paramamixoviridae, includes respiratory viral pathogens. Here we report the identification and genetic characterization of a respirovirus in an Alpine chamois showing interstitial pneumonia associated with catarrhal bronchopneumonia. The full-genome characterization of this respirovirus, named ChamoisRV/IT2014, revealed low similarities to caprine respirovirus (77.1%), bovine respirovirus (74.5%) and human respirovirus (72.0%). The phylogenetic analyses based on the full-length genome sequence of the novel isolate and reference respirovirus strains showed that ChamoisRV/IT2014 clustered with caprine respirovirus but formed a separate branch. The phylogenetic tree topology of complete large protein amino acid sequences, representing the current species demarcation criterion for Respirovirus genus, showed a 0.05 branch length of ChamoisRV/IT2014 sequence between the nearest node and the tip of the branch, suggesting that this virus belongs to a novel species. This new isolate in a new host species raises several questions to be addressed on the epidemiological role of chamois and the risks of cross-transmission between wild ruminants and livestock.